Risk factors of colorectal cancer in middle-aged and elder adults in China: findings from the China health and retirement longitudinal study - Zhang, Lin; Zhang, Yuyan; Huo, Yujia; Zhao, Yang; Xu, Aimin; Liu, Zhining; Hong, Qiaojun; Tu, Huiming; Huang, Junjie; Liu, Li (Frontiers in Molecular Biosciences, 2025)
ObjectiveThis study aims to identify risk factors of colorectal cancer in a middle-aged and elder Chinese population over 45 years old and to provide evidence for preventing colorectal cancer in China.MethodThe China Health and Retirement Longitudinal Study (CHARLS) is a nationally representative cohort used for research on demography, lifestyle and characteristics of colorectal cancer population. The logistic regression model was used to estimate the odds ratio (OR) and corresponding confidence interval (95% CI) using the maximum likelihood method. Univariate logistic regression was performed with the ORs of each risk factor and its association with incidence of colorectal cancer. Risk factors significant in univariate logistic regression were further evaluated by multivariate logistic regression. Cox proportional hazards model estimated the hazard ratio (HR) of each risk factor and its association with incidence of colorectal cancer.ResultsIn the univariable analysis, sex (OR = 2.31, 95% CI: 1.00–5.36, p = 0.05), smoking (OR = 2.30, 95% CI: 1.03–5.13, p = 0.04), age of quit drinking (OR = 1.07, 95% CI: 1.01–1.14, p = 0.02) and chronic lung disease (OR = 2.79, 95% CI: 1.11–6.99, p = 0.03) were associated with colorectal cancer which was also included in the multivariable analysis. However, probably because of the small sample size of colorectal cancer patients, no indicator was confirmed to be risk factor of colorectal cancer in the multivariable logistic regression. The univariate analysis of the Cox model indicated that smoking (HR = 2.30, 95%: 1.03–5.13, p = 0.04) and chronic lung disease (HR = 2.79, 95%: 1.11–6.97, p = 0.03) were associated with incidence of colorectal cancer. Similar to the results of multiple linear regression, no indicator was confirmed to be risk factors of incidence of colorectal cancer in the multivariable Cox model.ConclusionIn the univariate analysis, we identified significant associations between colorectal cancer and factors such as smoking and chronic lung disease. However, these associations did not hold in the multivariate analysis due to limitations in sample size. This suggests the need for further validation of these potential risk factors in larger-scale studies.